2004
DOI: 10.1097/01.psy.0000138119.12956.99
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Changes in the Serum Brain-Derived Neurotrophic Factor in Anorexia Nervosa and Obesity

Abstract: The BDNF changes observed in AN and obesity are likely secondary adaptive mechanisms aimed at counteracting the change in energy balance that occurs in these syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
3
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 29 publications
8
71
3
6
Order By: Relevance
“…Because the serum BDNF levels have been reported to change according to age, 31 body weight, BMI, 32 depression, 16,17 metabolic disorders, including diabetes mellitus, [19][20][21] and regular exercise, 33,34 we adjusted the model for these potential confounding factors. The association between the serum BDNF levels and dyssomnia remained statistically significant even after adjusting for these confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Because the serum BDNF levels have been reported to change according to age, 31 body weight, BMI, 32 depression, 16,17 metabolic disorders, including diabetes mellitus, [19][20][21] and regular exercise, 33,34 we adjusted the model for these potential confounding factors. The association between the serum BDNF levels and dyssomnia remained statistically significant even after adjusting for these confounders.…”
Section: Discussionmentioning
confidence: 99%
“…In the study on Monteleone et al increased BDNF levels have been observed in the serum of obese women compared with those in healthy women. The level of BDNF has been positively correlated with BMI and weight [14]. Many studies show the correlation between Val homozygotes and greater BMI in comparison to Met carriers in both adults and children in many ethnicities [13,18,30,31].…”
Section: Brain-derived Neurotrophic Factor Val66met Polymorphism In Cmentioning
confidence: 99%
“…The methionine allele is also associated with a greater risk of developing eating disorders, such as bulimia nervosa and binge-eating [26]. Also decreased BDNF levels have been reported in women with anorexia nervosa [14]. Some studies prove the connection between BDNF depletion and greater BMI, by demonstrating lower food intake and greater energy expenditure after administrating exogenous BDNF into the brain [27][28][29].…”
Section: Brain-derived Neurotrophic Factor Val66met Polymorphism In Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies have shown that serum BDNF levels are increased in obese women and decreased in women with anorexia nervosa compared with healthy individuals (119). Epidemiological evidence suggests that polymorphisms in BDNF may affect weight; the Val66Met BDNF polymorphism is associated with a lower BMI in healthy subject compared with healthy individuals with alternate polymorphisms (64).…”
Section: Molecular Mechanisms Of Adaptive Responses To Oxidative Stressmentioning
confidence: 99%